Evaluation of the Microbial Diversity in Amyotrophic Lateral Sclerosis Using High-Throughput Sequencing - Fang, Xin; Wang, Xin; Yang, Shaoguo; Meng, Fanjing; Wang, Xiaolei; Wei, Hua; Chen, Tingtao (Frontiers in Microbiology, 2016)
More and more evidences indicate that diseases of the central nervous system have been seriously affected by fecal microbes. However, little work is done to explore interaction between amyotrophic lateral sclerosis (ALS) and fecal microbes. In the present study, high-throughput sequencing method was used to compare the intestinal microbial diversity of healthy people and ALS patients. The principal coordinate analysis, Venn and unweighted pair-group method using arithmetic averages (UPGMA) showed an obvious microbial changes between healthy people (group H) and ALS patients (group A), and the average ratios of Bacteroides, Faecalibacterium, Anaerostipes, Prevotella, Escherichia, and Lachnospira at genus level between ALS patients and healthy people were 0.78, 2.18, 3.41, 0.35, 0.79, and 13.07. Furthermore, the decreased Firmicutes/Bacteroidetes ratio at phylum level using LEfSE (LDA > 4.0), together with the significant increased genus Dorea (harmful microorganisms) and significant reduced genus Oscillibacter, Anaerostipes, Lachnospiraceae (beneficial microorganisms) in ALS patients, indicated that the imbalance in intestinal microflora constitution had a strong association with the pathogenesis of ALS.